2020
DOI: 10.1136/bcr-2019-233993
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellitis as a rare manifestation of scrub typhus fever

Abstract: Scrub typhus is a mite-borne rickettsial disease caused by Orientia tsutsugamushi, a gram-negative coccobacilli transmitted through the bite of chigger mite. Scrub typhus has diverse clinical manifestations, often presenting either as a simple febrile illness or as a complicated multi-organ dysfunction. Neurological complications in scrub typhus are diverse but their exact incidence is unknown. Cerebellitis is another rare neurological manifestation associated with scrub typhus. Here, we report the case of a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Approximately 20%–25% of patients with scrub typhus suffer from neurological complications, making this an important part of the clinical constellation. [ 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 ...…”
Section: R Esultsmentioning
confidence: 99%
“…Approximately 20%–25% of patients with scrub typhus suffer from neurological complications, making this an important part of the clinical constellation. [ 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 ...…”
Section: R Esultsmentioning
confidence: 99%
“…MRI may or may not be normal. 7,12 Our case showed T2/FLAIR hyperintensity involving bilateral cerebellum. Scrub typhus response to doxycycline treatment is dramatic.…”
Section: Discussionmentioning
confidence: 57%
“…Previously Gupta et al 7 and Mahajan et al 8 have also reported isolated cerebellitis as a complication of scrub typhus. The likely pathophysiology is microangiopathy leading to focal or disseminated vasculitis or perivasculitis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The median duration of onset ranges from 3 to 22 days from the start of fever, consistent with our patient’s development of neurological dysfunction on day 10 of illness. Apart from meningitis and meningoencephalitis, other CNS manifestations include cerebellitis, cranial nerve palsies, transverse myelitis, transient parkinsonism, encephalomyelitis, infarctions and haemorrhages 8 9…”
Section: Discussionmentioning
confidence: 99%